P129 IBD care in the UK: A comprehensive, novel service assessment with feedback from 10, 222 patients and 166 NHS organisations to inform a vision for quality improvement. (27th May 2021) - Wakeman, R; Ainley, R; Arnott, I D; Barrett, K J; Bell, G; Berry, S; Bhatnagar, G; Blackwell, J; Bloom, S; Bramwell, C; Brookes, M J; Burman, A; et al.
Abstract: Background: The IBD Benchmarking Tool, comprising an online Service Self-Assessment and Patient Survey, has provided a unique and comprehensive picture of Inflammatory Bowel Disease (IBD) care across the UK. The aim was to evaluate current local service performance to facilitate future quality improvement. Methods: The IBD Patient Survey (PS) ran from July to November 2019 and the Service Self-Assessment (SSA) from October 2019 to January 2020. Detailed views were collected of the quality of IBD care from patient and clinician perspectives, measured against the UK IBD Standards 2019. 1 The IBD UK National Report will be published in April 2021. Results: 10, 222 patients completed the PS. 89% (9, 100/10, 222) had found it hard to cope with having Crohn's or Colitis over the previous year. 72% (6, 954/9, 640) rated the quality of their care as excellent, very good or good and 28% (2, 686/9, 640) rated the quality of their care as fair or poor. The top three factors that predicted how highly people with IBD rated their quality of care were: feeling supported by a team of specialists; having regular reviews; and discussing wider life goals and priorities, as part of planning their care. 26% (535/2, 089) had waited more than a year for their diagnosis. 41% (849/2, 087) had visited Accident & Emergency at least once before being diagnosed. 32% (656/2, 057) were not offered any information about their condition when diagnosed. 91% (8, 284/9, 099) did not have a personalised care plan. Over the previous 12 months, 70% (6, 732/9, 574) had one or more flares and 72% (1, 622/2, 250) of inpatient admissions were unplanned. A key finding from the SSA (166 centres: 134 adult, 32 paediatric) was that no adult IBD services reported meeting the IBD Standards' recommendation for whole time equivalent (WTE) staffing across the IBD team. Where services reported meeting the WTE for IBD nurse specialists, patients were more likely to rate the quality of their care highly and to have regular clinical review of their Crohn's or Colitis. Conclusion: The results highlight four key areas for change: improvements in diagnosis and information provision; personalised care and support for self-management; faster access to specialist advice and treatment; and effective multidisciplinary team (MDT) working. The Report sets out recommendations for action in each of these areas. To our knowledge, this is the first time that healthcare professionals and patients have assessed care against a common set of standards. The IBD Benchmarking Tool provides location-matched service performance and patient experience as an exemplar for others to follow. Reference: Kapasi R et al. Frontline Gastroenterology. 2020 May 1;11(3):178–87.